The Effect of Leadership Style on Financial Performance: A Case of Telecommunication Companies in Jordan - Al-Smadi, Arkan Walid Mohammad (2011)
With the advent of the technological revolution, economic globalization and the fundamental change of the social production method, human capital and social capital has become the key factors for a business organization to achieve competitive advantage (Li and Hu, 2007). This paper discusses the effect of leadership types on telecommunication organizational financial performance in Jordan. In other words, the study attempts to investigate whether there is a significant relationship between leadership types and organizational financial performance in selected telecommunication organizations in Jordan. The number of respondent is 120 managers of four organizations in Amman- Jordan. Their perspectives were translated into reports based on transformational. transactional and situational leadership styles. Based on regression analysis, it is clearly seen that there is only one independent variable that is significant which is transformational leadership that affecting the telecommunication organizational financial performance in Jordan.